Unveiling new phases of the Standard Model Higgs potential - Florian Goertz; Álvaro Pastor-Gutiérrez (European Physical Journal C: Particles and Fields)
Abstract We present evidence for new phases of the Standard Model Higgs potential. We study the Standard Model physical trajectory accounting for the Higgs curvature mass with the mass-dependent functional renormalisation group. New unstable and non-trivially stable phases are found at energies above the Planck scale and below the Abelian Landau pole. While the first aggravates the well-known metastable phase and threatens the viability of the Standard Model extrapolated to arbitrary scales, the latter can provide a well-defined ultraviolet completion. We investigate the phase diagram as a function of the top quark pole mass and study the effect of new physics through a scalar singlet portal coupling. The new non-trivial phase appears below the Planck scale in extensions of the Standard Model seeking stable trajectories. These findings have a significant impact on existing model building.